Effects of the flooding gradient on tree community diversity in varzea forests of the purus river, central Amazon, Brazil - Luize, Bruno Garcia; Silva, Thiago Sanna Freire [UNESP]; Wittmann, Florian; Assis, Rafael Leandro de; Venticinque, Eduardo Martins (Wiley-Blackwell, 2015)
Amazonian floodplain forests have remarkable variation in tree diversity and structure related to flood duration. We assessed how floodplain forests respond to the continuum flooding gradient and found that Fisher's values vary up to seven times across the landscape.
Keywords: Environmental gradient; Flood pulse; Floodplain forests; Wetlands